Mitofusin‐2 regulates leukocyte adhesion and β2 integrin activation. Issue 4 (8th September 2021) - Liu, Wei; Hsu, Alan Y.; Wang, Yueyang; Lin, Tao; Sun, Hao; Pachter, Joel S.; Groisman, Alex; Imperioli, Matthew; Yungher, Fernanda Wajnsztajn; Hu, Liang; Wang, Penghua; Deng, Qing; et al.
Abstract: Neutrophils are critical for inflammation and innate immunity, and their adhesion to vascular endothelium is a crucial step in neutrophil recruitment. Mitofusin‐2 (MFN2) is required for neutrophil adhesion, but molecular details are unclear. Here, we demonstrated that β2 ‐integrin‐mediated slow‐rolling and arrest, but not PSGL‐1‐mediated cell rolling, are defective in MFN2‐deficient neutrophil‐like HL60 cells. This adhesion defect is associated with reduced expression of fMLP (N‐formylmethionyl‐leucyl‐phenylalanine) receptor FPR1 as well as the inhibited β2 integrin activation, as assessed by conformation‐specific monoclonal antibodies. MFN2 deficiency also leads to decreased actin polymerization, which is important for β2 integrin activation. Mn 2+ ‐induced cell spreading is also inhibited after MFN2 knockdown. MFN2 deficiency limited the maturation of β2 integrin activation during the neutrophil‐directed differentiation of HL60 cells, which is indicated by CD35 and CD87 markers. MFN2 knockdown in β2‐integrin activation‐matured cells (CD87 high population) also inhibits integrin activation, indicating that MFN2 directly affects β2 integrin activation. Our study illustrates the function of MFN2 in leukocyte adhesion and may provide new insights into the development and treatment of MFN2 deficiency‐related diseases. Graphical Abstract: Identification of MFN2 as a key regulator of leukocyte adhesion, integrin activation, actin polymerization, and maturation.